2019
DOI: 10.2196/preprints.14549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of Serious Games to Increase Physical Activity in Children With a Chronic Disease: Systematic Review With Meta-Analysis (Preprint)

Abstract: BACKGROUND Physical activity (PA) is important for children with a chronic disease. Serious games may be useful to promote PA levels among these children. OBJECTIVE The primary purpose of this systematic review was to evaluate the effectiveness of serious games on PA levels in children with a chronic disease. METHODS … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In contrast, Akber et al [23] did not find a significant improvement in the mean daily step count of pediatric patients with CKD. Bossen et al [33] stated that serius games (webbased or exergame) are not effective to increase the PA level of children with chronic diseases. However, homebased or intradialytic exergames with Nintendo Wii were found to be effective in increasing daily PA in pediatric kidney transplant and adult HD patients [12,27].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Akber et al [23] did not find a significant improvement in the mean daily step count of pediatric patients with CKD. Bossen et al [33] stated that serius games (webbased or exergame) are not effective to increase the PA level of children with chronic diseases. However, homebased or intradialytic exergames with Nintendo Wii were found to be effective in increasing daily PA in pediatric kidney transplant and adult HD patients [12,27].…”
Section: Discussionmentioning
confidence: 99%
“…[2]. Using a serious game to learn children with special disorders, for instance, children with autism confirmed that learning of vocabulary items among children with autism enhanced significantly when they experience this category of the game [4], [5]. Moreover, physical activities using a serious game for children with a chronic disease may have some positive impact on the children to promote physical activity levels among these children [2].…”
Section: Introductionmentioning
confidence: 99%